Recycled fine aggregate self-compacting high-performance concrete and preparation method thereof
By optimizing the concrete components and processes, combined with the carbonization treatment of regenerated fine aggregates, the application of regenerated fine aggregates in high-performance concrete is solved, and high-performance, environmentally friendly, self-contained concrete is achieved, suitable for various building structures.
Patent Information
- Application Number
- CN202510049686.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
The difficulty in effectively using recycled fine aggregates in the prior art has resulted in limited application of their high-performance concrete and cannot meet the demand for high-performance concrete in building structures.
By optimizing the components and preparation process of concrete, cement, slag, fly ash, expansion agent and other ingredients are combined with high-performance water reducing agents, and carbonize the regenerated fine aggregates to improve their physical properties.
It significantly improves the self-concentration and compressive strength of concrete, extends the service life of building structures, promotes the resource utilization of building waste, and supports the sustainable development of building concepts.
Smart Images

Figure CN119874286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a self-compacting high-performance concrete with recycled fine aggregate and a preparation method thereof. Background Art
[0002] Concrete refers to an artificial stone made by mixing cement as the main cementitious material with water, sand, gravel, and chemical admixtures and mineral admixtures when necessary, in appropriate proportions, and through uniform mixing, compacting, forming, curing and hardening. Concrete is mainly divided into two stages and states: the plastic state before coagulation and hardening, that is, fresh concrete or concrete mixture; the hard state after hardening, that is, hardened concrete or concrete.
[0003] However, with the rapid development of the construction industry, the problem of construction waste disposal has become increasingly prominent. Traditional treatment methods often use landfill or stacking, which not only occupies a large amount of land resources, but may also cause long-term pollution to the environment. Therefore, how to achieve effective recycling and reuse of construction waste has become a hot topic in current research. Recycled fine aggregate, as an aggregate obtained by crushing, screening and other processes of construction waste, has potential resource value. Because recycled fine aggregate usually contains high impurities and water absorption, its performance is often difficult to meet the requirements of high-performance concrete.
[0004] Therefore, there is an urgent need for a concrete that can fully utilize recycled fine aggregate while maintaining high performance, which has important practical significance and application value. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a self-compacting high-performance concrete with recycled fine aggregate and a preparation method, aiming to improve the workability and mechanical properties of concrete by optimizing the components and preparation process of concrete, while realizing the resource utilization of construction waste. At the same time, the obtained concrete has excellent self-compacting properties and mechanical strength, and is suitable for various building structures, including bridges, high-rise buildings and infrastructure projects, which not only improves the performance of concrete, but also promotes environmental protection and sustainable development.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] A self-compacting high-performance concrete with recycled fine aggregate, comprising the following components by mass per unit volume:
[0008] Cement: 324~432kg / m 3 ;
[0009] Water: 156~176kg / m 3 ;
[0010] Slag: 45~60kg / m3 ;
[0011] Fly ash: 45~60kg / m 3 ;
[0012] Recycled fine aggregate: 502.5~538.5kg / m 3 ;
[0013] Water reducing agent: 2.04~7.5kg / m 3 ;
[0014] Expansion agent: 36~48kg / m 3 ;
[0015] Limestone powder: 45~60kg / m 3 .
[0016] Preferably, the recycled fine aggregate self-compacting high performance concrete specifically comprises the following components:
[0017] The total amount of cementitious materials is 450kg / m 3 The total amount of the gel material is the sum of the amount of cement, slag, fly ash and expansion agent, and the water is 176kg / m 3 , cement is 324kg / m 3 , slag is 45kg / m 3 , fly ash is 45kg / m 3 , machine-made sand: 884kg / m 3 , regenerated sand is 361.5kg / m 3 , waste sand is 177kg / m 3 , expansion agent is 36kg / m 3 , water reducing agent is 2.04kg / m 3 , limestone powder is 45kg / m 3 .
[0018] Preferably, the recycled fine aggregate self-compacting high performance concrete further comprises the following components:
[0019] The total amount of cementitious materials is 600kg / m 3 , water is 156kg / m 3 , cement is 432kg / m 3 , slag is 60kg / m 3 , fly ash is 60kg / m 3 , machine-made sand: 859kg / m 3 , regenerated sand is 348.75kg / m 3 , waste sand is 153.75kg / m 3 , expansion agent is 48kg / m 3 , water reducing agent is 7.5kg / m3 , limestone powder is 60kg / m 3 .
[0020] Preferably, the cement is P·O 42.5R ordinary Portland cement, and the chemical components of the cement include by weight percentage:
[0021] SiO2 21.20wt%;
[0022] Al2O34.81wt%;
[0023] Fe2O3 2.81wt%;
[0024] CaO 61.69wt%;
[0025] MgO 2.37wt%;
[0026] SO3 2.64wt%;
[0027] Na2O eq 0.55wt%, of which Na2O eq =Na2O+0.658K2O;
[0028] LOI 1.51 wt%.
[0029] Preferably, the recycled fine aggregate is formed by mixing machine-made sand, regenerated sand and waste stone sand in a ratio of 60:25:15, and the obtained recycled fine aggregate mixed sand has a fineness modulus of 2.4. The regenerated sand is discarded prefabricated components from a construction waste recycling plant, and the particle size of the regenerated sand is 0.075 mm to 4.75 mm.
[0030] Preferably, the water reducer is HPWR-R polycarboxylate high performance water reducer, and the slag is S95 grade slag.
[0031] Preferably, the expansion agent is SCEA-I expansion agent, and the chemical composition of the expansion agent includes by weight percentage:
[0032] SiO2 8.74wt%;
[0033] Al2O32.98wt%;
[0034] Fe2O3 3.53wt%;
[0035] CaO 74.51wt%;
[0036] MgO 4.23wt%;
[0037] SO3 1.31wt%;
[0038] S 0.31wt%;
[0039] Cl - 0.004wt%.
[0040] Preferably, the chemical composition of the limestone powder includes by weight percentage:
[0041] SiO2 2.50wt%;
[0042] Al2O3 0.60wt%;
[0043] Fe2O3 0.36wt%;
[0044] CaO 54.03wt%;
[0045] MgO 0.54wt%;
[0046] SO3 0.01wt%;
[0047] Na2O eq 0.084wt%, of which Na2O eq =Na2O+0.658K2O;
[0048] LOI 41.60wt%.
[0049] Preferably, the fly ash is Class I fly ash, and the chemical composition of the fly ash includes, by weight percentage:
[0050] SiO2 46.89wt%;
[0051] Al2O3 24.53wt%;
[0052] Fe2O3 13.55wt%;
[0053] CaO 1.35wt%;
[0054] MgO 2.07wt%;
[0055] SO3 0.63wt%;
[0056] Na2O eq 1.57wt%, of which Na2O eq =Na2O+0.658K2O;
[0057] LOI 5.68wt%.
[0058] The present invention also provides a method for preparing the above-mentioned recycled fine aggregate self-compacting high-performance concrete, comprising the following steps:
[0059] S1. Prepare materials, including P·O 42.5R ordinary Portland cement, water, HPWR-R polycarboxylate high performance water reducer, SCEA-I expansion agent, and mineral admixture, wherein the mineral admixture consists of slag and fly ash;
[0060] S2. Preparation and carbonization treatment of recycled fine aggregate:
[0061] S21, mixing machine-made sand: regenerated sand: waste stone sand in a ratio of 60:25:15 to obtain mixed sand;
[0062] S22, pre-soak the mixed sand in a saturated calcium hydroxide solution for 24 hours, stirring it every 6 hours to ensure that the aggregate is evenly soaked;
[0063] S23, after the soaking is completed, the mixed sand is drained out, and then the mixed sand is placed in an oven, dried at 55-65°C for 2h, and finally cooled to room temperature and taken out;
[0064] S24. After completing S23, the treated mixed sand is subjected to carbonization treatment for 12 to 48 hours at an optimal carbonization pressure of 0.5 MPa to obtain recycled fine aggregate;
[0065] S3. According to the set raw material ratio, the material prepared in S1 is mixed with the recycled fine aggregate prepared in S2, and the mixture is stirred evenly, molded, and cured to obtain a finished product.
[0066] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0067] (1) The raw material ratio design of the present invention significantly improves the self-compactness and compressive strength of concrete by comprehensively using multiple ingredients such as cement, slag, fly ash, and expansion agent, combined with a high-performance water reducer. This improvement ensures that the concrete can better fill the mold during the pouring process, reduces the generation of voids and defects, and thus improves the overall quality and durability of the final component. In addition, after the specific recycled fine aggregate is carbonized, the porosity of the recycled fine aggregate is reduced, and the permeability of chloride ions and gases is reduced, thereby enhancing the mechanical properties of the concrete, enabling it to resist erosion and aging of the external environment during long-term use, and extending the service life of the building structure.
[0068] (2) The present invention uses recycled fine aggregate to replace traditional natural aggregate, and uses recycled sand from construction waste, etc., which promotes the recycling of resources, not only reduces the demand for natural resources, but also effectively reduces the burden of construction waste on the environment, thereby supporting the concept of sustainable development. At the same time, the concrete has the characteristics of high performance, environmental protection, self-compacting, etc., and is suitable for various engineering fields that require high-performance concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0070] Figure 1 The present invention is a flow chart of a method for preparing self-compacting high-performance concrete with recycled fine aggregate.
[0071] Figure 2 The present invention is a flow chart of the preparation and carbonization treatment of recycled fine aggregate. DETAILED DESCRIPTION
[0072] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0073] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0074] like Figure 1 As shown, the present invention provides a method for preparing recycled fine aggregate self-compacting high-performance concrete, comprising the following steps:
[0075] S1. Prepare materials, including P·O 42.5R ordinary Portland cement, water, HPWR-R polycarboxylate high performance water reducer, SCEA-I expansion agent, and mineral admixture, wherein the mineral admixture consists of slag and fly ash;
[0076] S2. Preparation and carbonization of recycled fine aggregate;
[0077] S3. According to the set raw material ratio, the material prepared in S1 is mixed with the recycled fine aggregate prepared in S2, and the mixture is stirred evenly, molded, and cured to obtain a finished product.
[0078] Reference Figure 2 , the preparation and carbonization treatment of recycled fine aggregate includes the following steps:
[0079] S21, mixing machine-made sand: regenerated sand: waste stone sand in a ratio of 60:25:15 to obtain mixed sand;
[0080] S22, pre-soak the mixed sand in a saturated calcium hydroxide solution for 24 hours, stirring it every 6 hours to ensure that the aggregate is evenly soaked;
[0081] S23, after the soaking is completed, the mixed sand is drained out, and then the mixed sand is placed in an oven, dried at 55-65°C for 2h, and finally cooled to room temperature and taken out;
[0082] S24. After completing S23, the treated mixed sand is subjected to carbonization treatment for 12 to 48 hours at an optimal carbonization pressure of 0.5 MPa to obtain recycled fine aggregate;
[0083] In the above-mentioned carbonization process, the physical properties of the mixed sand were improved after carbonization treatment. The pre-immersion carbonization treatment of saturated calcium hydroxide reduced the water absorption rate of the mixed sand by 10.28% to 21.79%, increased the apparent density by 0.22% to 0.46%, and decreased the crushing index by 12.4% to 22.74%. The strengthening effect of the pre-immersion carbonization treatment of saturated calcium hydroxide is significant. When the carbonization pressure is 0.5MPa and the carbonization time increases from 12h to 48h, the physical properties of the mixed sand show an increasing trend that is positively correlated with the carbonization time, and all show the best physical properties at 48h. It can be inferred that the optimal carbonization conditions for saturated calcium hydroxide pre-immersion carbonization are 0.5MPa and 48h.
[0084] In the above preparation method, a self-compacting high-performance concrete with recycled fine aggregate, measured by mass per unit volume, comprises the following components:
[0085] Cement: 324~432kg / m 3 ;
[0086] Water: 156~176kg / m 3 ;
[0087] Slag: 45~60kg / m 3 ;
[0088] Fly ash: 45~60kg / m 3 ;
[0089] Recycled fine aggregate: 502.5~538.5kg / m 3 ;
[0090] Water reducing agent: 2.04~7.5kg / m 3 ;
[0091] Expansion agent: 36~48kg / m 3 ;
[0092] Limestone powder: 45~60kg / m 3 .
[0093] The cement is P·O 42.5R ordinary Portland cement produced by Chongqing Xiaonanhai Cement Plant, and the chemical composition of the cement includes by weight percentage:
[0094] SiO2 21.20wt%;
[0095] Al2O34.81wt%;
[0096] Fe2O3 2.81wt%;
[0097] CaO 61.69wt%;
[0098] MgO 2.37wt%;
[0099] SO3 2.64wt%;
[0100] Na2O eq 0.55wt%, of which Na2O eq =Na2O+0.658K2O;
[0101] LOI 1.51 wt%.
[0102] In addition, the recycled fine aggregate is made of machine-made sand, regenerated sand and waste stone sand in a ratio of 60:25:15, and the obtained recycled fine aggregate mixed sand has a fineness modulus of 2.4; wherein the machine-made sand is medium sand from Zone II produced in Banan District, Chongqing, with a fineness modulus of 2.8, a moisture content of 1.7%, and an apparent density of 2660 kg / m 3 , bulk density 1640kg / m 3 , stone powder content is 11.1%, and crushing index is 17%; the regenerated sand is the discarded prefabricated components of the construction waste recycling plant, and the particle size of the regenerated sand is 0.075mm~4.75mm; the waste stone sand is sampled from the concrete tank truck cleaning sedimentation tank of Chongqing Tuohai Concrete Co., Ltd., and the waste slag aging time is about 24h. The mixing station waste slag is processed by a series of physical means such as rapid drying and grinding.
[0103] In the above raw material composition, the water reducer is HPWR-R polycarboxylate high performance water reducer, with a water reduction rate of 30%, a water bleeding rate of 25%, an air content of 2.7%, a solid content of 13.65%, a pH of 4.6, and a density of 1.031 kg / m 3 The slag is S95 grade slag produced by Chongqing Yuhong Recycling Resources Co., Ltd., with a specific surface area of 453m 2 / kg. The expansion agent is SCEA-I expansion agent produced by Chongqing Beibei Sansheng New Material Technology Co., Ltd., and the chemical composition of the expansion agent includes by weight percentage:
[0104] SiO2 8.74wt%;
[0105] Al2O32.98wt%;
[0106] Fe2O3 3.53wt%;
[0107] CaO 74.51wt%;
[0108] MgO 4.23wt%;
[0109] SO3 1.31wt%;
[0110] S 0.31wt%;
[0111] Cl - 0.004wt%.
[0112] The limestone powder is produced by Chongqing Fuling Daye Building Materials Co., Ltd. The chemical composition of the limestone powder includes the following by weight percentage:
[0113] SiO2 2.50wt%;
[0114] Al2O3 0.60wt%;
[0115] Fe2O3 0.36wt%;
[0116] CaO 54.03wt%;
[0117] MgO 0.54wt%;
[0118] SO3 0.01wt%;
[0119] Na2O eq 0.084wt%, of which Na2O eq =Na2O+0.658K2O;
[0120] LOI 41.60wt%.
[0121] The fly ash is Class I fly ash produced by Chongqing Luohuang Power Generation Co., Ltd. The chemical composition of the fly ash includes, by weight percentage:
[0122] SiO2 46.89wt%;
[0123] Al2O3 24.53wt%;
[0124] Fe2O3 13.55wt%;
[0125] CaO 1.35wt%;
[0126] MgO 2.07wt%;
[0127] SO3 0.63wt%;
[0128] Na2O eq 1.57wt%, of which Na2O eq =Na2O+0.658K2O;
[0129] LOI 5.68wt%.
[0130] Example 1
[0131] In this embodiment, the recycled fine aggregate self-compacting high performance concrete specifically includes the following components:
[0132] The total amount of cementitious materials is 450kg / m 3 The total amount of the gel material is the sum of the amount of cement, slag, fly ash and expansion agent, and the water is 176kg / m 3 , cement is 324kg / m 3 , slag is 45kg / m 3 , fly ash is 45kg / m 3 , machine-made sand: 884kg / m 3 , regenerated sand is 361.5kg / m 3 , waste sand is 177kg / m 3 , expansion agent is 36kg / m 3 , water reducing agent is 2.04kg / m 3 , limestone powder is 45kg / m 3 .
[0133] The preparation method of the above raw material composition is:
[0134] a) preparing materials, including P·O 42.5R ordinary Portland cement, water, HPWR-R polycarboxylate high performance water reducing agent, SCEA-I expansion agent, and mineral admixture, wherein the mineral admixture consists of slag and fly ash;
[0135] b) Preparation and carbonization treatment of recycled fine aggregate:
[0136] c) mixing machine-made sand: regenerated sand: waste stone sand in a ratio of 60:25:15 to obtain mixed sand;
[0137] d) Pre-soak the mixed sand in a saturated calcium hydroxide solution for 24 hours, stirring it every 6 hours to ensure that the aggregate is evenly soaked;
[0138] e) After the soaking is completed, the mixed sand is drained out, and then the mixed sand is placed in an oven, dried at 60° C. for 2 hours, and finally cooled to room temperature and taken out; then the treated mixed sand is carbonized for 48 hours at an optimal carbonization pressure of 0.5 MPa to obtain recycled fine aggregate;
[0139] f) According to the set raw material ratio, the prepared materials are mixed with the prepared recycled fine aggregate, stirred evenly, molded, and cured to obtain a finished concrete product with grade C30.
[0140] Example 2
[0141] In this embodiment, the recycled fine aggregate self-compacting high performance concrete specifically includes the following components:
[0142] The total amount of cementitious materials is 600kg / m 3 , water is 156kg / m 3 , cement is 432kg / m 3 , slag is 60kg / m 3 , fly ash is 60kg / m 3 , machine-made sand: 859kg / m 3 , regenerated sand is 348.75kg / m 3 , waste sand is 153.75kg / m 3 , expansion agent is 48kg / m 3 , water reducing agent is 7.5kg / m 3 , limestone powder is 60kg / m 3 .
[0143] The preparation method of the above raw material composition is:
[0144] a) preparing materials, including P·O 42.5R ordinary Portland cement, water, HPWR-R polycarboxylate high performance water reducing agent, SCEA-I expansion agent, and mineral admixture, wherein the mineral admixture consists of slag and fly ash;
[0145] b) Preparation and carbonization treatment of recycled fine aggregate:
[0146] c) mixing machine-made sand: regenerated sand: waste stone sand in a ratio of 60:25:15 to obtain mixed sand;
[0147] d) Pre-soak the mixed sand in a saturated calcium hydroxide solution for 24 hours, stirring it every 6 hours to ensure that the aggregate is evenly soaked;
[0148] e) After the soaking is completed, the mixed sand is drained out, and then the mixed sand is placed in an oven, dried at 60° C. for 2 hours, and finally cooled to room temperature and taken out; then the treated mixed sand is carbonized for 48 hours at an optimal carbonization pressure of 0.5 MPa to obtain recycled fine aggregate;
[0149] f) According to the set raw material ratio, the prepared materials are mixed with the prepared recycled fine aggregate, stirred evenly, molded, and cured to obtain a finished concrete product with grade C60.
[0150] The above-mentioned Example 1 and Example 2 were subjected to performance tests, and the obtained results are shown in Table 1.
[0151] Table 1 Test results of concrete performance of different grades
[0152]
[0153] Referring to Table 1, the grade C30 concrete prepared in Example 1 and the grade C60 concrete prepared in Example 2 both exhibit good slump and slump expansion, which indicates that the self-compacting high-performance concrete with recycled fine aggregate of the present invention has excellent fluidity and self-compacting ability, and can fill all corners in the formwork without vibration, thereby improving construction efficiency and quality. At the same time, the concrete prepared in the two examples has a small height difference between the middle and sides and a vibration segregation rate of less than 5%, which proves the uniformity and stability of the concrete mixture, which helps to reduce defects in the construction process and improve the durability of the structure. In addition, the 7d and 28d strengths of the grade C60 concrete prepared in Example 2 are significantly higher than those of the grade C30 concrete prepared in Example 1, and both exhibit higher strength in the early stage, which proves that the concrete of the present invention has good mechanical properties and crack resistance, and thus the concrete of the present invention has the characteristics of high performance, environmental protection, self-compacting, etc., and is suitable for various engineering fields requiring high-performance concrete.
[0154] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0155] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A self-compacting high-performance concrete with recycled fine aggregate, characterized in that: Measured by mass per unit volume, it includes the following components: Cement: 324~432kg / m 3 ; Water: 156~176kg / m 3 ; Slag: 45~60kg / m 3 ; Fly ash: 45~60kg / m 3 ; Recycled fine aggregate: 502.5~538.5kg / m 3 ; Water reducing agent: 2.04~7.5kg / m 3 ; Expansion agent: 36~48kg / m 3 ; Limestone powder: 45~60kg / m 3 .
2. The self-compacting high performance concrete with recycled fine aggregate according to claim 1, characterized in that: The recycled fine aggregate self-compacting high performance concrete specifically comprises the following components: The total amount of cementitious materials is 450kg / m 3 The total amount of the gel material is the sum of the amount of cement, slag, fly ash and expansion agent, and the water is 176kg / m 3 , cement is 324kg / m 3 , slag is 45kg / m 3 , fly ash is 45kg / m 3 , machine-made sand: 884kg / m 3 , regenerated sand is 361.5kg / m 3 , waste sand is 177kg / m 3 , expansion agent is 36kg / m 3 , water reducing agent is 2.04kg / m 3 , limestone powder is 45kg / m 3 .
3. The self-compacting high performance concrete with recycled fine aggregate according to claim 2, characterized in that: The recycled fine aggregate self-compacting high performance concrete further specifically comprises the following components: The total amount of cementitious materials is 600kg / m 3 , water is 156kg / m 3 , cement is 432kg / m 3 , slag is 60kg / m 3 , fly ash is 60kg / m 3 , machine-made sand: 859kg / m 3 , regenerated sand is 348.75kg / m 3 , waste sand is 153.75kg / m 3 , expansion agent is 48kg / m 3 , water reducing agent is 7.5kg / m 3 , limestone powder is 60kg / m 3 .
4. The self-compacting high performance concrete with recycled fine aggregate according to claim 1, characterized in that: The cement is P·O 42.5R ordinary Portland cement, and the chemical components of the cement include by weight percentage: SiO2 21.20wt%; Al2O34.81wt%; Fe2O3 2.81wt%; CaO 61.69wt%; MgO 2.37wt%; SO3 2.64wt%; Na2O eq 0.55wt%, of which Na2O eq =Na2O+0.658K2O; LOI 1.51 wt%.
5. The self-compacting high performance concrete with recycled fine aggregate according to claim 1, characterized in that: The recycled fine aggregate is formed by mixing machine-made sand, regenerated sand and waste stone sand in a ratio of 60:25:
15. The fineness modulus of the obtained recycled fine aggregate mixed sand is 2.
4. The regenerated sand is discarded prefabricated components from a construction waste recycling plant. The particle size of the regenerated sand is 0.075 mm to 4.75 mm.
6. The self-compacting high performance concrete with recycled fine aggregate according to claim 1, characterized in that: The water reducer is HPWR-R polycarboxylate high performance water reducer, and the slag is S95 grade slag.
7. The self-compacting high performance concrete with recycled fine aggregate according to claim 1, characterized in that: The expansion agent is SCEA-I expansion agent, and the chemical composition of the expansion agent includes by weight percentage: SiO2 8.74wt%; Al2O32.98wt%; Fe2O3 3.53wt%; CaO 74.51wt%; MgO 4.23wt%; SO3 1.31wt%; S 0.31wt%; Cl - 0.004wt%。 8. The self-compacting high performance concrete with recycled fine aggregate according to claim 1, characterized in that: The chemical composition of the limestone powder includes by weight percentage: SiO2 2.50wt%; Al2O3 0.60wt%; Fe2O3 0.36wt%; CaO 54.03wt%; MgO 0.54wt%; SO3 0.01wt%; Na2O eq 0.084wt%, of which Na2O eq =Na2O+0.658K2O; LOI 41.60wt%.
9. The self-compacting high performance concrete with recycled fine aggregate according to claim 1, characterized in that: The fly ash is Class I fly ash, and the chemical composition of the fly ash includes, by weight percentage: SiO2 46.89wt%; Al2O3 24.53wt%; Fe2O3 13.55wt%; CaO 1.35wt%; MgO 2.07wt%; SO3 0.63wt%; Na2O eq 1.57wt%, of which Na2O eq =Na2O+0.658K2O; LOI 5.68wt%.
10. The method for preparing a self-compacting high performance concrete with recycled fine aggregate according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Prepare materials, including P·O 42.5R ordinary Portland cement, water, HPWR-R polycarboxylate high performance water reducer, SCEA-I expansion agent, and mineral admixture, wherein the mineral admixture consists of slag and fly ash; S2. Preparation and carbonization treatment of recycled fine aggregate: S21, mixing machine-made sand: regenerated sand: waste stone sand in a ratio of 60:25:15 to obtain mixed sand; S22, pre-soak the mixed sand in a saturated calcium hydroxide solution for 24 hours, stirring it every 6 hours to ensure that the aggregate is evenly soaked; S23, after the soaking is completed, the mixed sand is drained out, and then the mixed sand is placed in an oven, dried at 55-65°C for 2h, and finally cooled to room temperature and taken out; S24. After completing S23, the treated mixed sand is carbonized for 12 to 48 hours at an optimal carbonization pressure of 0.5 MPa to obtain recycled fine aggregate; S3. According to the set raw material ratio, the material prepared in S1 is mixed with the recycled fine aggregate prepared in S2, and the mixture is stirred evenly, molded, and cured to obtain a finished product.